Development of Rhetoric by Antique Theologues (Journal of Philosophy Culture and Political Science, 2020)
At present, Classic Rhetoric and Modern Neo-Rhetoric have established major fundamentals of the effective, powerful, and persuasive speech. Secular public speaking has demonstrated significant achievements in various genres, and yet, since the nowadays society sets cultural and educational goals to shape high moral personality, it sharpens the focus to both secular and spiritual eloquence.Research Goal: analysis of the development of Rhetoric by antique teologues and further inheritance as from Ancient Rus to our days. Findings of the analysis of the development of Rhetoric by antique theologies prove it necessary to use certain rhetoric tools in sermons in churches along with the parallel adherence to the basic tenets of homiletics to contribute to the effectiveness of the verbal influence onthe audience. Rhetoric mastership of the homiletic eloquence and capturing public speaking skills of a secular speechmaker should be combined in an effort to shape the spiritual culture of a personality and serve as an instrument to overcome aggression in speaking which so often led to bloody wars and reciprocal devastation.Key words: public speaking skills, rhetoric, sophistry, homiletics, antique.